2016
DOI: 10.1055/s-0042-115570
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive MRI-Based Liver Iron Quantification: Methodic Approaches, Practical Applicability and Significance

Abstract: Pathophysiology of iron overload ▼Normal iron content plays an important role in the physiological processes of the human body. A disturbance to the precisely regulated iron metabolism system has serious consequences. Therefore, for example, iron overload results in oxidative damage to membrane lipids and proteins and in DNA damage that can cause mitochondrial and lysosomal dysfunction, changes in gene expression, and changes in tumor suppressor genes (p53). Organ damage due to iron overload primarily affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Additionally, it is known that liver fat and iron can be quantified by MRI. 62,63 It is expected that with a better IVIM imaging protocol with more b values and better image postprocessing, differentiation of early-stage fibrotic liver from healthy liver should have increased reliability. The use of Bayesian prediction, incorporating relevant findings from the available methods, is also a promising technique for liver fibrosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that liver fat and iron can be quantified by MRI. 62,63 It is expected that with a better IVIM imaging protocol with more b values and better image postprocessing, differentiation of early-stage fibrotic liver from healthy liver should have increased reliability. The use of Bayesian prediction, incorporating relevant findings from the available methods, is also a promising technique for liver fibrosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that liver fat and iron can be quantified by MRI. 62, 63 It is expected that with better IVIM imaging protocol with more b-values and better image post-procession, differentiation of early stage fibrotic liver from healthy liver should have increased reliability. The use of Bayesian prediction, incorporating relevant findings from the available methods, is also a promising technique for liver fibrosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The question which requires important attention is to detect F1 and F2 stage liver fibrosis. Additionally, liver fat and iron can reliably be quantified by MRI [55, 56]. The use of Bayesian prediction, incorporating relevant findings from the available methods, is also a promising technique for liver fibrosis evaluation [57].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance units 1-4 correspond to four other machines located in the same city. shown that it overestimates patients with moderate overload [25][26][27] and recently it has been replaced by a new T2* relaxometry method (www. MRQuantif.org) that is also able to perform SIR calculations.…”
Section: Signal Intensity Ratio Methodsmentioning
confidence: 99%
“…MRQuantif.org) that is also able to perform SIR calculations. Additionally, the Spanish Society of Abdominal Imaging (SEDIA, www.sedia.es) has developed a specific mathematical model to estimate LIC that shows a good correlation with relaxometry techniques [26,27] (https://imagemed. univ-rennes1.fr/en/mrquantif/quantif.php).…”
Section: Signal Intensity Ratio Methodsmentioning
confidence: 99%